Mean Reduction in Pain Score in Patients of Plantar Fasciitis after Triamcinolone Injection in Comparison to Autologous Blood Injection - Imtiaz Ahmed, Saad riaz, M Nadeem Kashmiri, Shahzad Anjum, Obaid ur Rahman, Nayyer Qayyum , Imtiaz Ahmed, Saad riaz, M Nadeem Kashmiri, Shahzad Anjum, Obaid ur Rahman, Nayyer Qayyum; Imtiaz Ahmed Shakir, Saad Riaz, Muhammad Nadeem Kashmiri, Shahzad Anjum, Obaid Ur Rehman, Nayyar Qayyum, (Journal of Rawalpindi Medical College, 2018)
Background: To compare mean reduction in pain score in patients of plantar fascitis treated with triamcinolone injection in comparison to autologous blood injection. Methods: This randomized controlled trail included 100 patients with plantar fasciitis. Base line visual analogue score (VAS) was calculated for each patients. 50 patients received triamcinolone injection and 50 patients’ received ABI. VAS was calculated 6 weeks after treatment. The mean reduction in VAS in both groups was compared (p-value < 0.05 was taken as significant). Results: The mean base line pain on VAS score of the patients in triamcinolone group 7.63 + 1.24 and in autologous blood injection group was 7.19 + 1.78. Statistically, there was no significant difference between the two groups. (p-value > 0.05). The mean of VAS score of the patients after treatment was in triamcinolone group was 2.74 + 1.34and in autologous blood injection group was 4.28 + 2.08. Statistically, there was significant difference between the two groups. (p-value < 0.05). The mean of reduction in VAS score of the patients after treatment was in triamcinolone group was 3.22 + 1.79 and in autologous blood injection group was 1.93 + 2.34. Statistically, there was no significant difference between the two groups. (p-value > 0.05). Conclusion: Both triamcinolone injection and autologus blood injection can reduce the pain score significantly among patients with plantar fascitis. However, more reduction in pain score was seen in patients of plantar fasciitis treated with Triamcinolone injection as compared to autologous blood injection.